PEMBUATAN TEPUNG GADUNG (DIOSCOREA HISPIDIA DENNST) MELALUI PROSES PERENDAMAN MENGGUNAKAN EKSTRAK KUBIS FERMENTASI - Catur Ayu Wulandari; Wikanastri Hersoelistyorini; Nurhidajah Nurhidajah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Yam tubers besides for consumption directly, can also be processed into flour. Soaking treatment using fermented cabbage extract was predicted to give effect on the reduction of HCN level of yam flour. The purpose of this research is to know the effect of soaking using fermented cabbage extract to the level of proximate, amylose, HCN and the characteristic of organoleptic of yam flourincluding color, flavor, and texture. This research was an experiment and designed using RAL method. Data analysis was using ANOVA test and Post Hoc advanced test with level of confidence 95 %, whereas organoleptic was using Friedman test and advanced test using Wilcoxon. Proximateand HCN level were determined based on the best treatment of organoleptic test and amylose level, where organoleptic was determined based on panelist assessment results. Analysis result of amylose showed the lowest percentage 28.32% on 96 hours of soaking. Analysis result for the lowest HCN level was 43.09 ppm on 96 hours of soaking. Assessment result of organoleptic showed the bestacceptance level, which is on 96 hours of soaking (2.78). The conclusion are the longer soaking led to the lower level of amylose, HCN, but increase the characteristic of organoleptic and increase protein nutrition content of yam flour.Key words: yam flour, fermented cabbage extract, HC